IMPLEMENTASI PRINSIP-PRINSIP CEDAW DALAM PENANGANAN KASUS KEKERASAN TERHADAP PEREMPUAN DI SPEK-HAM SOLO - Prawira P, Yudanto; Cahyandaru, Prabowo (PARENTAL, 2013)
This research aimed to find out the implementation of Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) principles to the management of women violence case by SPEK-HAM Solo and to find out the factors affecting the effectiveness of the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW). This study was an empirical descriptive law research. The research was taken place in the office of Solidaritas Perempuan untuk Kemanusiaan dan Hak Asasi Manusia (SPEK-HAM = Women Solidarity for Humanity and Human Rights) Solo. The types of data employed were primary and secondary data. Techniques of collecting data used were interview and library study, constituting books, legislation, document and etcetera. The technique of analysis employed was qualitative data analysis. Considering the research it could be found that the implementation of CEDAW to the management of violence against woman case had been consistent with CEDAW. The factors affecting the effectiveness of CEDAW implementation were firstly, regarding the law is good. Secondly, the law enforcers particularly police officer still transcended bureaucracy and procedure leading to delayed help giving. Thirdly, the infrastructure and facility used had been consistent with CEDAW. Fourthly, the low understanding of law among the members of society about CEDAW made the gender-based violence cases frequently befell the women in private or family domain.